Synovial fibroblast-miR-214-3p-derived exosomes inhibit inflammation and degeneration of cartilage tissues of osteoarthritis rats - Lai, Chenteng; Liao, Boyi; Peng, Song; Fang, Peng; Bao, Nirong; Zhang, Lei (Molecular and cellular biochemistry, 2023)
MicroRNAs (miRs) are regulators of number of cellular process. miRs enclosed within exosomes can be crucial regulators of intercellular signalling and could be an important biomarker of various age-associated disorders. Role of exosomal enclosed miRs in osteoarthritis (OA) chondrocytes and synovial fibroblasts (SFBs) remains poorly studied. Here, we profiled and studied the effect of synovial fluid-derived exosomal miRs on inflammation, survival, proliferation of chondrocyte in correlation with cartilage degeneration. Exosomes were isolated from synovial fluid collected from OA subjects and were analysed by transmission electron microscopy. miRs were isolated and were submitted to microarray profiling. Web-based PCR analysis was done. Chondrocyte proliferation and colony formation assay were performed. Apoptosis study was done by flow cytometer. Gene expression was done by qRT-PCR analysis and protein expression by western blot assay. Rat model of OA was created by operating the knee by anterior cruciate ligament and resection of medial menisci (ACLT + MMx) method. Micro-CT analysis, histological analysis, immunohistochemical staining, and TUNEL assay were also performed. About 17 miRs were found to be expressed differentially in the synovial fluid collected from the control and OA subjects. Microarray analysis confirmed, expression of miR-214-3p was significantly downregulated in the synovial fluid exosome of OA subjects. miR-214-3p mimic promoted proliferation of chondrocyte and suppressed apoptosis. Treatment also inhibited the levels of TNF-α, IL-1β and IL-6. SFB-miR-214-3p exosomes suppressed apoptosis and also inflammation in chondrocytes. In vivo study suggested that SFB-exosomal miR-214-3p from rats suppressed the formation of osteophytes, prevented degeneration of cartilage and exerted anti-inflammatory and anti-apoptotic effect in articular cartilage tissue. The findings suggested that SFB-miR-214-3p exosomes can ameliorate chondrocyte inflammation and degeneration of cartilage tissues. The study confirms therapeutic potential of SFB-miR-214-3p exosomes in treating OA.